2023
DOI: 10.1093/jas/skad074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weaning strategy and backgrounding management on growth performance, carcass characteristics, and mRNA expression in the longissimus muscle of beef steers

Abstract: We evaluate the effect of the weaning strategy (WS; early, 130 ± 21 d vs normal, 187 ± 20 d) and backgrounding management (BGM) on growth, carcass characteristics, and relative mRNA expression in the longissimus muscle (LM) of beef steers. One hundred and twenty Angus × SimAngus-crossbred steers (body weight (BW) = 130 ± 11.2 kg) were used in a randomized complete block design. Steers, blocked by age and BW, were randomly assigned to 1 treatment (2×2 factorial). Treatments consisted of early weaned (EW) or nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Early-weaned steers had a greater expression of ZFP423 during the backgrounding phase (d112), whereas normal-weaned steers had a greater expression of ZFP423 during the finishing phase (d 255). It was also observed that DLK1 expression was greater for steers that were backgrounded on concentrate-based diets than forages early in the backgrounding phase but not in the finishing phase [21]. The expression of transcription factors (PPARg and SREBP1c) was not altered, but their activators (PGC1a and SCAP) were down-regulated with concentrate feeding (PW120) compared to PW0.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Early-weaned steers had a greater expression of ZFP423 during the backgrounding phase (d112), whereas normal-weaned steers had a greater expression of ZFP423 during the finishing phase (d 255). It was also observed that DLK1 expression was greater for steers that were backgrounded on concentrate-based diets than forages early in the backgrounding phase but not in the finishing phase [21]. The expression of transcription factors (PPARg and SREBP1c) was not altered, but their activators (PGC1a and SCAP) were down-regulated with concentrate feeding (PW120) compared to PW0.…”
Section: Discussionmentioning
confidence: 95%
“…A change in ZFP423 but not Pref1 provides mixed results regarding if changes in adipocyte hyperplasia are involved in IMF deposition with concentrate feeding post-weaning. Others [21] have reported that feeding concentratebased diets during the post-weaning phase altered ZFP423 expression, but these changes were dependent on the time of weaning. Early-weaned steers had a greater expression of ZFP423 during the backgrounding phase (d112), whereas normal-weaned steers had a greater expression of ZFP423 during the finishing phase (d 255).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation